1977
DOI: 10.1007/bf02256517
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal fistulae and double pyloric canal

Abstract: Abstract. Four cases of endoscopically proven gastroduodenal fistulae (double pyloric canal) are presented, and ten case reports in the literature are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Endoscopy performed to confirm the lesion previously detected by X-ray and to ascertain its nature shows the two channels: the demon stration of their opening into the duodenum can be carried out by introduction of either polyethylene catheters (21) or the endoscope itself (27) into the two channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopy performed to confirm the lesion previously detected by X-ray and to ascertain its nature shows the two channels: the demon stration of their opening into the duodenum can be carried out by introduction of either polyethylene catheters (21) or the endoscope itself (27) into the two channels.…”
Section: Discussionmentioning
confidence: 99%
“…Hegedus et al (12) found 13 cases out of 7,932 radiological examinations within a period of 3 years (0.16%). In the first 8 months of 1978, 19 cases have been reported (12,13,17,21) and this is probably due to a greater awareness toward the problem. The case we describe has been detected out of an amount of 1,428 upper digestive endoscopies (0.09%).…”
mentioning
confidence: 99%
“…GDF is an interesting and rare condition with radiological appearances of an antral or ulcerating carcinoma, Crohn's disease or lymphoma . The presence of previous ulceration and scarring should aid in distinguishing it from a malignancy.…”
mentioning
confidence: 99%
“…However, some cases have been reported in which DP was evidently a congenital anomaly. [1][2][3][4][5] The first case of DP was detected endoscopically. 6 To date, there have been sporadic reports of more than 100 cases.…”
mentioning
confidence: 99%
“…However, about 20% of the patients underwent surgery because of refractory symptoms or other complications. 3,5,7,8 There is no long-term follow-up study of DP. 3,5,[7][8][9] The association of DP with other systemic diseases 8,9 and Helicobacter pylori infection 9 is not well characterized.…”
mentioning
confidence: 99%